KEMAMPUAN MENULIS TEKS EKSPOSISI SISWA KELAS VIII SMP NEGERI 1 TEMBILAHAN KOTA - Yuni Audina; Abdul Razak; Mangatur Sinaga (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is entitled the ability to write exposition text of eighth grade students of SMP Negeri 1 Tembilahan Kota. The purpose of this study was to describe the level of the ability to write exposition text of eighth grade students of SMP Negeri 1 Tembilahan Kota, and to describe the differences in the ability to write exposition text of eighth grade students of SMP Negeri 1 Tembilahan Kota in each sample group class. The data of this research are the results of the exposition writing ability test of the eighth grade students of SMP Negeri 1 Tembilahan Kota which is divided into 2 classes and consists of 45 populations with a sample of 40 students. The results of the study after testing using the one-sample chi square test, the ability to write exposition text is the same as the comparative value of 69. The ability to write exposition text of eighth grade students of SMP Negeri 1 Tembilahan Kota is moderate. Then, testing was done using an Mann Whitney test, to determine the differences in the ability to write exposition text of eighth grade students of SMP Negeri 1 Tembilahan Kota between sample groups. The result is that there is no difference in the ability to write exposition text between classes of sample groups.Keywords: abilities, exposition text, students